Confirming Delivery: Understanding the Role of the Hospitalized Patient in Medication Administration Safety. (April 2014) - Macdonald, Marilyn T.; Heilemann, MarySue V.; MacKinnon, Neil J.; Lang, Ariella; Gregory, David; Gurnham, Mary Ellen; Fillatre, Theresa
The purpose of our study was to gain an understanding of current patient involvement in medication administration safety from the perspectives of both patients and nursing staff members. Administering medication is taken for granted and therefore suited to the development of theory to enhance its understanding. We conducted a constructivist, grounded theory study involving 24 patients and 26 nursing staff members and found that patients had the role of confirming delivery in the administration of medication. Confirming delivery was characterized by three interdependent subprocesses: engaging in the medication administration process, being "half out of it" (patient mental status), and perceiving time. We believe that ours is one of the first qualitative studies on the role of hospitalized patients in administering medication. Medication administration and nursing care systems, as well as patient mental status, impose limitations on patient involvement in safe medication administration.